2012
DOI: 10.32674/jis.v2i2.527
|View full text |Cite
|
Sign up to set email alerts
|

Grounded Identities, Transient Lives: The Emergence of International Student Voices in an Era of Cosmopolitan Learning

Abstract: This paper is an exploration of the identity negotiations of two international undergraduate students at a public research university in the United States. Studying abroad constitutes a culturally contested space for educational sojourners, with ruptures that require constant sense-making and negotiations of identities as students attempt to combine the foreign and the familiar. Situational contexts, interpersonal interactions, and the imagination all determine what students learn and how that learning occurs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, international and multilingual students can be regarded as transnationals living between worlds, connected to both their home and host countries, and working towards future academic mobility (Gargano, 2012). Their sociocultural histories and shifting identities will also influence how they respond to the learning context and the assigned work in a certain classroom.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, international and multilingual students can be regarded as transnationals living between worlds, connected to both their home and host countries, and working towards future academic mobility (Gargano, 2012). Their sociocultural histories and shifting identities will also influence how they respond to the learning context and the assigned work in a certain classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Because there appears to be less information written about sense making, the next subsection will touch upon studies that show the ways in which international students make sense of their experiences taking courses in the United States from a more general perspective. Gargano (2012) showed that international students need to make sense of their home identities and reflect on cultural changes or barriers that may exist in the university they are studying in. To truly understand the needs of these students, researchers need to go beyond "quantitative inventories and surveys" and engage the students in critical conversations (Gargano, 2012, p. 154).…”
Section: Sense Making In Information Literacy Coursesmentioning
confidence: 99%
“…To truly understand the needs of these students, researchers need to go beyond "quantitative inventories and surveys" and engage the students in critical conversations (Gargano, 2012, p. 154). There are many important lessons to take from this study, including that it is important to understand how international students create their own cultural identities and how that can impact their work (Gargano, 2012). Krsmanovic (2020) used Berry's (2017) acculturation model to show how students adapt or integrate in different ways when they study abroad.…”
Section: Sense Making In Information Literacy Coursesmentioning
confidence: 99%